The Role of Autonomous Agent-Based ISA (Information Systems in Accounting) in Managing the Decentralized Accounting Cycle: A Socio-Technical Systems Approach - Afwil Jazil (PT. Hafasy Dwi Nawasena, 2025)
This study aims to analyze the role of autonomous agent-based Information Systems in Accounting (ISA) in managing the decentralized accounting cycle using a socio-technical systems approach in the private sector. The background of this research lies in the increasing demand for speed, accuracy, and transparency in financial reporting within the competitive digital business ecosystem. This study adopts a qualitative method through in-depth interviews and document analysis, supported by thematic analysis for data interpretation. The findings reveal that autonomous agent-based ISA enhances transaction-processing efficiency, reduces recording errors, strengthens internal control, and provides real-time financial information for strategic decision-making. However, its effectiveness depends on the alignment between technological and social dimensions of organizations, including digital competence readiness, employee acceptance of automation, and role restructuring. This research concludes that agent-based accounting systems are not merely digital tools, but strategic infrastructures that shape long-term competitive advantage for private-sector firms